Relationship between clinical manifestations and serological profile in patients affected by Systemic Lupus Erythematosus - Nicola, Stefania; Borrelli, Richard; Corradi, Federica; Lo Sardo, Luca; Badiu, Iuliana; Romito, Alessandra; Rashidy, Nicolò; Quinternetto, Anna; Mazzola, Marina; Meli, Federico; Saracco, Elena; Vitali, Ilaria; et al. (Frontiers in Immunology, 2024)
Background Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder characterized by a variety of both signs and symptoms; it mainly affects women of childbearing age, with an estimated prevalence of 24/100,000 people in Europe and North America. SLE is often described as an antibodies-driven disease as its clinical manifestations are usually associated with the presence or the absence of specific antibodies. Objectives To evaluate clinical manifestations in patients with SLE and to assess the relationship with the presence of specific antibodies by using real-world data. Methods A retrospective study was performed; the 2019 EULAR/ACR Classification Criteria for Systemic Lupus Erythematosus were used to classify patients with SLE. Data concerning serological profiles (which included Antinuclear antibodies – ANA, anti dsDNA, anti-Ro/SS-A, anti-La/SS-B, anti-Smith) were gathered along with medical records of clinical manifestations. Complement levels were also tested for possible clinical correlations. χ² or Fisher’s exact tests were utilized to establish associations between autoantibodies and symptoms. The odds ratios (OR) and their 95% confidence intervals (CI) were computed. No correction was made for multiple testing; only a p-value 0.01 ≤ was considered significant. Results One-hundred and twenty-seven patients (n=127, mean age 53.43 ± 14.02) were enrolled in this study. Anti-dsDNA antibodies were found to be statistically significant for both malar rash and proteinuria; anti-Ro/SSA antibodies showed an association with photosensitivity and pericarditis; furthermore, a strong association was found between anti-Ro antibodies and proteinuria, but only if anti-dsDNA antibodies were present as well. Patients who tested positive for anti-La/SSB antibodies correlated with a threefold increase in the risk of developing pericarditis. Lastly, anti-Smith appeared to be associated with NPSLE as well as an increased risk for both autoimmune hemolytic anemia and thrombocytopenia. Conclusions In our study, many associations confirmed those found in previous studies; however, new relationships between antibodies and clinical manifestations were found thus indicating the need for additional evaluations to assess these correlations further.